2012
DOI: 10.1590/s1516-35982012000400018
|View full text |Cite
|
Sign up to set email alerts
|

Performance of lambs supplemented with fodder salt Gliricidia sepium (Jacq.)

Abstract: -The objective of this experiment was to evaluate productive performance of lambs fed different levels of Gliricidia sepium (Jacq.) in the making of gliricidia forage salt. A total of 30 180-day-old male crossbred Santa Inês lambs of 25 kg body weight were confined in 1 m 2 stalls, fed Tifton-85 (Cynadon spp.) hay, fodder salts and water ad libitum. The experimental design was randomized, composed of six repetitions of five treatments. The formulation of gliricidia forage salt was 0 (100% NaCl), 93, 95, 97 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…The higher intakes of CP and EE observed in the present study in the group of lambs supplemented with GFS compared with those receiving only NaCl is attributed to the consumption of Gliricidia in the fodder salt, since this legume had a higher CP and EE content in its composition than TGH did (Table 1). This finding is similar to those observed by Cirne et al (2012), who obtained higher CP and EE intake by animals supplemented with GFS; by Gonçalves et al (2008), who observed greater CP intake in animals receiving supplementation based on fodder salt from Leucaena and cassava shoots; and by , who recorded a higher CP intake for animals supplemented with fodder salt from Leucaena and cassava shoots. ) were not influenced (P>0.05) by the experimental diets (Table 5).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The higher intakes of CP and EE observed in the present study in the group of lambs supplemented with GFS compared with those receiving only NaCl is attributed to the consumption of Gliricidia in the fodder salt, since this legume had a higher CP and EE content in its composition than TGH did (Table 1). This finding is similar to those observed by Cirne et al (2012), who obtained higher CP and EE intake by animals supplemented with GFS; by Gonçalves et al (2008), who observed greater CP intake in animals receiving supplementation based on fodder salt from Leucaena and cassava shoots; and by , who recorded a higher CP intake for animals supplemented with fodder salt from Leucaena and cassava shoots. ) were not influenced (P>0.05) by the experimental diets (Table 5).…”
Section: Resultssupporting
confidence: 89%
“…There was an increasing linear effect (P<0.05) for GFS intake as the levels of inclusion of Gliricidia were increased, with every 10 g/kg −1 of inclusion in the fodder salt increasing total GFS intake by 0.010 kg. The average GFS intake of 0.118 kg day −1 was similar to the 0.102 kg day −1 found by Cirne et al (2012), who evaluated the performance of feedlot Santa Inês mixed-breed lambs supplemented with GFS; and higher than the 0.066 kg day −1 observed by in Santa Inês mixed-breed sheep supplemented with GFS. However, for animals supplemented with fodder salt from cassava shoots and Leucaena, and Gonçalves et al (2008) , respectively.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Additionally, Gliricidia can be used to incorporate nitrogen into the soil (Schwendener et al, 2007) and acts as a biological control agent for certain pests (Sivira et al, 2011). According to Cirne et al (2012), this species performs well when fed to feedlot sheep.…”
Section: Introductionmentioning
confidence: 99%